STATUS OF HEART RATE VARIABILITY IN SNAKE BITE - RAJESH KUMAR.A; MUHIL. M; SENTHIL KUMARAN; THIRUMALAIKOLUNDUSUBRAMANIAN.P (International Journal of Pharma and Bio Sciences, 2016)
Snake bite is the most common problem in tropical and subtropical countries. Snakebite is related to highest mortality of poorly developed countries mainly the farmers suffered a lot. As per the World Health Organization’s list the snake bite is neglected tropical diseases. Immediately after the snake bite toxicity of the snake venom enters into circulation and affects various parts of the body. The envenomation acts on the Autonomic nervous system, and affects the heart and reduces the heart rate. And also the venom directly act on the cardiac muscle and decreases the force of contraction which reduces heart rate. Analysis of Heart Rate variability is one of the non-invasive electrocardiographic markers to find out the changes HRV in snake bite patients. In snake bite envenomation the increases HRV (P-Value is <0.05) is considered as the statistically significant. We conclude that autonomic control of the heart rate measured by heart rate variability was altered on acute action of snake envenomation. Initially there wasparasympathetic dominance in snake bite and treatment with antivenom lead to sympathetic dominance.